Rekonsepsi Paradigma Bimbingan Konseling Yang Memandirikan - Asep Solikin (Anterior Jurnal, 2016)
Guidance and counseling is a proactive and systemic effort in facilitating individual to achieve his/her optimal development, the development of effective behavioral, the development of environmental development, and the enhancement of the functioning of the individual in his/her environment. Currently, it has occurred the change of the approach of paradigm in guiding and counseling, that is from the approach that oriented to the traditional, remedial, clinical, and centered on the counselor to the development and preventive oriented approach, namely Developmental Guidance and Counseling, or Comprehensive Guidance and Counseling. This study on paradigm of guidance and independent counseling used descriptive approach or describing a problem based on a literature review of existing literature or guiding books that related to the current study. In the implementation of this writing focused on the study of literature by using historical study, which is trying to explore the concepts and paradigm of guidance and independent counseling (which is trying to explore the concepts and paradigm of independent guidance and counseling), through studies and book sources that are relevant to the discussion of this study. The new paradigm of the re-concept of guidance and counseling can be done in a systematic and programmed to be more independent in a counselor. There are two inevitability that should be prioritized in the re-concept processes, namely; Tawhid education as a center of education and teaching that will give the philosophy of the other elements and moral education as the mission of the educational objectives.